1980
DOI: 10.1128/iai.27.2.435-443.1980
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of the duration and magnitude of protection against Salmonella infection afforded by various vaccines with antibody titers

Abstract: Groups of mice were immunized with optimal doses of the following vaccines of Salmonella typhimurium W118-2: acetone-killed cells, lipopolysaccharide, ribosomes, and live cells. At 3 weeks, 1 month, 2 months, 4 months, or 6 months postimmunization, sera were collected from control and vaccinated animals, and the anti-lipopolysaccharide and whole-cell agglutination titers of the sera were determined. Other groups of similarly vaccinated mice were tested for resistance to infection by challenging with live W118-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1981
1981
1997
1997

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…First, passive transfer of immune mouse serum to outbred mice did not protect them from lethal challenge (5). Second, outbred mice infected 3 weeks previously with a sublethal dose of S. typhimurium were resistant to lethal challenge, although little (17) or no (2) anti-Salmonella 0 antibodies were demonstrable in their sera. However, recent studies from this laboratory (20) suggested that B cells may, in fact, be required for the expression of resistance to S. typhimurium.…”
mentioning
confidence: 97%
“…First, passive transfer of immune mouse serum to outbred mice did not protect them from lethal challenge (5). Second, outbred mice infected 3 weeks previously with a sublethal dose of S. typhimurium were resistant to lethal challenge, although little (17) or no (2) anti-Salmonella 0 antibodies were demonstrable in their sera. However, recent studies from this laboratory (20) suggested that B cells may, in fact, be required for the expression of resistance to S. typhimurium.…”
mentioning
confidence: 97%
“…Salmonella live vaccines provide a more durable immunity than nonviable vaccines, despite the fact that ribosomal vaccines afforded a comparatively long-term protection [2,3]. Our early work [3] has shown that the duration of salmonella immunity correlated with the persistent reactivity to salmonella antigens of T ceils from immunized mice, although such an in vitro T-cell response decreased with time after immunization.…”
Section: Discussionmentioning
confidence: 99%
“…Undoubtedly, unfractionated spleen cells of immune mice are competent in adoptive immunity [1], but a single population of immune cells was less effective. In addition, a similar controversy surrounds the question of why only living cells of S. typhimurium can provide a longer-lasting immunity to murine typhoid, although there is evidence that salmonella ribosomal vaccines may also induce a similar type of protection [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…al, 1982) and polyvalent radiovaccine (Chander and Lewis 1987). However, all these studies were carried out to develop an effective vaccine to combat salmonellosis and the major limitation with these vaccines was the short (Angerman and Eisenstein 1980). This limitation is of no consequence in poultry as broiler chicks are normally sacrificed by the sixth week.…”
Section: Enumeration Of Salmonella In Spleen and Livermentioning
confidence: 99%